Differences in Sleep Quantity in Babies Aged 3-6 Months between before and after the Massage Babies at Posyandu Anggrek Pojok Village of Kediri City in 2023 - Sutrisni; Halimatus Saidah; Putri Wahyu Wigati (Journal of Global Research in Public Health, 2023)
Sleep is one of the growth factors for babies. Where during sleep all the muscles stop working and the nerves work according to their position. Putting a baby to sleep is not easy, there are many things we have to do. Sometimes babies’ sleep is not optimal, this is due to many factors, one of which is because the body is tired after excessive activity. From the initial survey conducted by researchers at Posyandu anggrek Pojok Village, Kediri City in 2023, there were 10 babies, babies who were fussy and after having a baby massage experienced a sound sleep (40%), babies who had not had a baby massage and experienced disturbances in their sleep (60 %). This shows that babies who have not had massage experience problems sleeping. The aim of this study was to determine the difference in sleep quantity in babies aged 3-6 months between before and after baby massage at Posyandu anggrek Pojok Village, Kediri City in 2023. The design used in this research was pre-experiment, with pre-test and post-test methods. The variables measured in this study were (Y1) the quantity of baby sleep before the baby massage and (Y2) the quantity of baby sleep after the baby massage. This research uses the Wilcoxon Signed Ranks Test statistical test. The results of the research from a total of 20 respondents showed that the baby’s sleep quantity was good after baby massage and previously the baby’s sleep quantity was insufficient (80%), while the baby’s sleep quantity was good after baby massage and previously the baby’s sleep quantity was sufficient (20%). The results of data analysis using the Wilcoxon Signed Ranks Test statistical test at a significance level of α = 0.05 showed statistical test results with a significance value of p = 0.000 < 0.05, which means that H0 was rejected, meaning there was a difference in the quantity of baby sleep between before and after baby massage. at Posyandu anggrek Pojok Village, Kediri City in 2023. Based on the results of this research, it is hoped that the respondent’s family will carry out baby massage because the benefits of baby massage are very good for optimizing growth and development in babies.